Comparing the effects of mitochondrial targeted and localized antioxidants with cellular antioxidants in human skin cells exposed to UVA and hydrogen peroxide. Issue 1 (10th October 2013) - Oyewole, Anne O.; Wilmot, Marie‐Claire; Fowler, Mark; Birch‐Machin, Mark A.
Abstract : Skin cancer and aging are linked to increased cellular reactive oxygen species (ROS), particularly following exposure to ultraviolet A (UVA) in sunlight. As mitochondria are the main source of cellular ROS, this study compared the protective effects of mitochondria‐targeted and ‐localized antioxidants (MitoQ and tiron, respectively) with cellular antioxidants against oxidative stress‐induced [UVA and hydrogen peroxide (H2 O2 )] mitochondrial DNA (mtDNA) damage in human dermal fibroblasts. With the use of a long quantitative PCR assay, tiron (EC50 10 mM) was found to confer complete (100%) protection ( P <0.001) against both UVA‐ and H2 O2 ‐induced mtDNA damage, whereas MitoQ (EC50 750 nM) provided less protection (17 and 32%, respectively; P <0.05). This particular protective effect of tiron was greater than a range of cellular antioxidants investigated. The nuclear factor erythroid 2‐related factor 2 (Nrf2) signaling pathway provides cellular protection against oxidative stress. An ELISA assay for the Nrf2 target gene heme oxygenase‐1 ( HO‐1 ) and studies using Nrf2 small interfering RNA both indicated that tiron's mode of action was Nrf2 independent. The comet assay showed that tiron's protective effect against H2 O2 ‐ induced nuclear DNA damage was greater than the cellular antioxidants and MitoQ ( P <0.001). This study provides a platform to investigate molecules with similar structure to tiron as potent and clinically relevant antioxidants.—Oyewole, A. O., Wilmot, M.‐C., Fowler, M., Birch‐Machin, M. A. Comparing the effects of mitochondrial targeted and localized antioxidants with cellular antioxidants in human skin cells exposed to UVA and hydrogen peroxide. FASEB J . 28, 485–494 (2014). www.fasebj.org